Effect of traffic volume and shoulder width towards crash cases at jalan Kuantan bypass - Norazlina, Ahmad Tajuddin (2018)
Kuantan Bypass is known for having a very high vehicles crash rate from year to year. Rapid development along the roads together with establishments of many new industrial areas in the road surrounding area have been observed as the main factor for this issue. This study aims to investigate the effect of vehicles and shoulder width towards high number of crash cases along Jalan Kuantan Bypass. Crashes occur due to several reasons which include drivers' negligence, road conditions, vehicle conditions and weather conditions. This thesis will mainly focus on 2 categories of data namely, vehicles and shoulder width. All data were collected on site during weekdays and weekend along 2.2 km road starts from signalized intersection near Wisma Belia until signalized intersection at Bukit Rangin. Relationship between traffic volume, shoulder width and crash cases was generated using multiple regression analysis. The model shows that the multiple regression is explaining the severity of crash by 61% (r-squared = 0.611) and it is proven that vehicles and shoulder width is statistically significant to the severity of crash (p = 0.0001, p < 0.001). The outcomes generated from this study is hope to give an insight to the Kuantan local authority in producing proper plan to solve the interruption of heavy vehicles to traffic flow at Jalan Kuantan Bypass.